2017
DOI: 10.12657/denbio.078.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the Salix lapponum L. population intended as a source of material for reintroduction

Abstract: Salix lapponum is a relict species that occurs in peat bogs. The most numerous population in Poland, which is located on Lake Bikcze, was selected as a source of plant material for genetic analysis to check if it could be used to translocate and establish new populations in the future. For this purpose, the genetic variability of five groups of plants, which were located 50 to 130 m away from one another, was assessed using the AFLP method. GenoType software did not indicate clonal individuals in the studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For example, in Europe, restoration programs involving habitats with rare species of the genus Salix are carried out in the United Kingdom [48], the Czech Republic [49], and Poland [50], among others. These programs are usually linked to the verification of methods that increase the effectiveness of conservation treatments and to multifaceted studies of factors affecting the stability of populations of endangered species [15][16][17]20,34,[51][52][53][54][55][56][57][58][59].…”
Section: Of 15mentioning
confidence: 99%
“…For example, in Europe, restoration programs involving habitats with rare species of the genus Salix are carried out in the United Kingdom [48], the Czech Republic [49], and Poland [50], among others. These programs are usually linked to the verification of methods that increase the effectiveness of conservation treatments and to multifaceted studies of factors affecting the stability of populations of endangered species [15][16][17]20,34,[51][52][53][54][55][56][57][58][59].…”
Section: Of 15mentioning
confidence: 99%
“…Pieces of S. lapponum shoots were collected from the largest population in eastern Poland, located in a peat bog by Lake Bikcze (51 • 22 724" N 023 • 02 563" E), at the end of April 2018. The population has a satisfactory sex ratio and high genetic variation [9], which indicates its ability to reproduce sexually. Shoot fragments 5 cm in length were collected from mother plants, which had been previously numbered and whose sex had been verified.…”
Section: Tissue Culture Initiation and Stabilizationmentioning
confidence: 99%
“…The results of genetic studies have also confirmed the absence of clones in populations of this species. However, there were no seedlings observed within the existing populations, most likely due to the unstable habitat conditions, in which seeds were unable to germinate [9].…”
Section: Introductionmentioning
confidence: 99%
“…This particular population was selected due to its size (the largest in Eastern Poland -about 300 individuals), the stable sex ratio (1:1) and optimal genetic structure (lack of clonal individuals) that confirms its proper functioning (Głębocka & Pogorzelec, 2017).…”
Section: Study Area and Populationmentioning
confidence: 99%